COMPETITIVENESS OF AGRICULTURAL ENTERPRISE: METHODOLOGY OF THE ANALYSIS OF DEFINITION - Boidunyk , V.R.; Boidunyk , N.M. (The actual problems of regional economy development, 2020)
The article considers the scientific approaches to the essence and interpretation of the concepts of "competitiveness", "industry competitiveness", "product competitiveness", and "enterprise competitiveness". The analysis of theoretical definitions of "enterprise competitiveness" allowed us to identify several approaches to its understanding. It is determined that today there are many interpretations of the concept of "enterprise competitiveness", but there is no single interpretation. It has been concluded that this category is characterized by a list of properties that are sufficient to reveal its theoretical foundations. It has been investigated that the concept of competitiveness is one of the main categories and is widely used in the theory and practice of economic sciences. It has been determined that the essential elements in the competition are competitive advantages and they can be created in different ways, so in order to quickly acquire them, it is necessary to classify them. The groups of competitive advantages of the enterprise activity are characterized and their division according to the sources of their origin into external and internal ones is carried out, they must meet certain requirements in terms of value. It has been studied that a competitive advantage is the presence of an agricultural enterprise or other business entity of any significance, which gives it an advantage over competitors. The main factors that ensure the formation of effective competitiveness of agricultural enterprises in market conditions have been analyzed. The main competitive advantages are identified, which should be answered as follows: to be unique; provide consumer benefits for customers and high profitability for the agricultural enterprise; be dynamic in nature, and be important for imitation by competitors.